Analysis of the Financial and Technical Feasibility of Erection a Herbal Medicine Factory Pt. Tugu Semar Production Using the Systematic Layout Planning Method - Nada, Muhammad Bisyri; Oetomo, Dedy Setyo; Hermawan, Asep (Sainteks: Jurnal Sain dan Teknik, 2024)
Abstract: With the increasing demand for herbal medicine and efforts to reduce the import value of herbal drugs, PT Tugu Semar Production plans to enhance production by establishing a new factory. The planning utilizes the Systematic Layout Planning (SLP) method and conducts a financial feasibility analysis related to the investment. The prospective location is in Blitar, with a production capacity of 100 liters or 500 bottles. The research also encompasses a financial feasibility analysis using capex data of Rp. 4,539,800,000 and first-year opex of Rp. 3,646,980,053. The financial feasibility analysis results in an Internal Rate of Return (IRR) of 21%, indicating the financial viability of the investment. With a significant IRR, the project estimates a return on investment within 4 years and 8 months. These findings provide a comprehensive insight into the success of herbal medicine factory planning using the SLP method and instill confidence that this investment holds high financial feasibility potential. The implications of this research are expected to offer strategic guidance to PT Tugu Semar Production in decision-making concerning the development of the herbal medicine factory in Blitar. Keywords: Systematic Layout Planning; NPV ; IRR ; PBP